Treatment of Helicobacter pylori infection: mainstream and innovations (Review of the literature and Russian gastroenterological association Advisory council resolution, May 19, 2017) - V. T. Ivashkin; I. V. Mayev; T. L. Lapina; A. A. Sheptulin; A. S. Trukhmanov; R. A. Abdulkhakov; S. A. Alekseyenko; N. N. Dekhnich; R. S. Kozlov; I. L. Klyaritskaya; S. A. Kurilovich; M. F. Osipenko; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present data of clinical trials, systematic reviews and metaanalyses which allow to optimize eradication therapy of Helicobacter pylori (H. pylori) infection. Summary. Standard triple therapy including proton pump inhibitor (PPI), clarithromycin and amoxicillin is the firstline treatment for H. pylori eradication. At prescription of standard triple therapy various measures increasing its efficacy should be utilized. Classical fourcomponent bismuth tripotassium dicitratebased treatment or quadrotherapy without bismuth including PPI, amoxicillin, clarithromycin and metronidazole may be alternative options for the first line eradication therapy. Quadrotherapy with bismuth tripotassium dicitrate is applied as the basic mode of second line therapy at failure of standard triple therapy. Alternative mode of the second line therapy includes PPI, levofloxacin and amoxicillin. Levofloxacinbased triple therapy can be prescribed only by specialist in gastroenterology at strict indications. Third line therapy is personalized according to the choice of the previous treatment modes. The choice of H. pylori eradication therapy in the Russian Federation is based on empirical approach. The rate of clarithromycin resistance of H. pylori strains in Russia does not exceed 15% in the majority of regional studies. There are data indicating absence of significant metronidazole resistance of H. pylori and low level of double clarithromycin and metronidazole resistance. Efficacy of H. pylori eradication therapy may be enhanced by increasing treatment duration to 14 days. Prescription of new generation PPI or increase of PPI dose are targeted to provide the maximum acid suppression, highly important for successful H. pylori infection eradication. Additional prescription of bismuth tripotassium dicitrate, probiotics or rebamipid increases efficacy of antihelicobacter therapy. Significant decrease of adverse events rate at H. pylori eradication treatment is reached at combined prescription of probiotics. Rebamipid may potentiate reparative processes in the stomach mucosa. Conclusion: Methods of H. pylori eradication optimization can be applied for enhancement of both standard triple therapy and other concomitant treatment modes, and the combination of these methods provides best result for the given patient.